2014
DOI: 10.2139/ssrn.2489875
|View full text |Cite
|
Sign up to set email alerts
|

How to Measure the Unsecured Money Market? The Eurosystem's Implementation and Validation Using TARGET2 Data

Abstract: Unconventional monetary policy measures included fixed-rate full allotment since October 2008; swap agreements with other central banks (e.g., Federal Reserve, Swiss National Bank); extension of the collateral framework; extension of the duration of the refinancing operations (e.g., year tenders starting July 2009 and three-year tenders starting December 2011); the introduction of the Covered Bond Purchase Program (May 2009), the Securities Market Program (May 2010), and the Outright Monetary Transactions (Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 10 publications
3
72
0
Order By: Relevance
“…Regarding the validity of the Furfine's method, Armantier and Copeland (2012) have questioned the results obtained when implementing Furfine's method. On the other hand, Arciero et al (2013) contrast results reported by Armantier and Copeland, and confirm the validity of Furfine's method conditional on a deep knowledge of the underlying data and the technical attributes of the system under analysis.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Regarding the validity of the Furfine's method, Armantier and Copeland (2012) have questioned the results obtained when implementing Furfine's method. On the other hand, Arciero et al (2013) contrast results reported by Armantier and Copeland, and confirm the validity of Furfine's method conditional on a deep knowledge of the underlying data and the technical attributes of the system under analysis.…”
Section: Introductionsupporting
confidence: 76%
“…This feature of the dataset avoids making some assumptions for identifying loans and refunds. For instance, following the algorithm's setup by Arciero et al (2013), we do not need to define minimum loan values and increments in loan values to filter out potential loans. As defining these two parameters is critical for minimizing false negatives and false positives (Arciero et al, 2013), working with filtered data should mitigate some serious sources of error.…”
Section: The Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of the Furfine algorithm at identifying interbank lending has been studied for a number of markets, including the Bank of England's CHAPS Sterling settlement system (cf Wetherilt et al, 2009 andAcharya and. Merrouche, 2013), Switzerland(Guggenheim and Kraenzlin, 2010), and the Eurosystem real-time gross settlement system, TARGET2(Arciero et al, 2013).…”
mentioning
confidence: 99%
“…Most of them are settled as over-thecounter (OTC) agreements, about which data is not systematically collected. Studies on interbank loan markets therefor often rely on data that is reconstructed from the observation of payments between banks (see, e.g., Arciero et al, 2013). The data that we analyze here is not from OTC transactions.…”
Section: Introductionmentioning
confidence: 99%